Supreme Court case law on the appeal system and the beginning of sentencing executing: the poverty of Brazilian comparative law - Fauzi Hassan Choukr (Revista Brasileira de Direito Processual Penal)
This paper aims to discuss the use, by the Supreme Brazilian Court, of the comparative method as a basis for its rationality about the moment when the penal sentencing must be executed and the penalty must be executed. After an analysis of the ways of the Court’s understanding on that subject, it will be appreciated how the comparative law was employed in the most recent decision on the subject, which was used with fragile methodological basis, so being used as an authoritative argument to support them.